2019
DOI: 10.15446/dyna.v86n210.74475
|View full text |Cite
|
Sign up to set email alerts
|

Reference framework for capabilities development in agricultural innovation systems

Abstract: Agricultural Innovation Systems (AIS) approach, arise as tool for better understanding dynamics and complexity of agricultural innovation. The dynamic approach of organizational capabilities development, is consolidated as a conceptual lens for AIS analysis, but not the systemic approach, which is considered emerging. The objective of this article is present a framework for AIS capability development, taking as a scientific reference, emerging economy countries experiences. A multi-dimensional methodology of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…For this study, we collected data from agricultural innovation systems, which are networks of actors (universities, research centres, territorial entities, enterprises, NGOs) working collaboratively (Galeano-Barrera et al, 2022). Universities play a central role in the collaboration between actors in innovation systems at the global level, through functions and roles such as knowledge brokering, supported by their social capital (Romero-Riaño et al, 2019). The heterogeneity of scientific collaboration networks is a facilitator of innovation diffusion and the impact of research results.…”
Section: Data Collection and Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, we collected data from agricultural innovation systems, which are networks of actors (universities, research centres, territorial entities, enterprises, NGOs) working collaboratively (Galeano-Barrera et al, 2022). Universities play a central role in the collaboration between actors in innovation systems at the global level, through functions and roles such as knowledge brokering, supported by their social capital (Romero-Riaño et al, 2019). The heterogeneity of scientific collaboration networks is a facilitator of innovation diffusion and the impact of research results.…”
Section: Data Collection and Case Selectionmentioning
confidence: 99%
“…We analyse the citation networks of authors and organizations in agricultural research in Colombia, as an academic contribution to the understanding of the productivity and impact of universities, as well as collaboration within this discipline. Data was extracted from the study conducted by Romero-Riaño et al (2019) corresponding to the census of institutions identified within the collaborative networks of Santander and Caldas for the period 2014-2018. A total of 154 universities comprises the dataset for the territory of Santander and 126 for Caldas.…”
Section: Data Collection and Case Selectionmentioning
confidence: 99%
“…Una CN está compuesta por diferentes actores como pueden ser organizaciones y/o personas que son en gran medida autónomas desde el aspecto jurídico o desde el marco legal, comúnmente con localización geográfica similar y probablemente heterogéneas en cuanto a su cultura, capital social y objetivos, siendo estos últimos los cuales en su mayoría llevan a una colaboración (Camarinha-Matos & Afsarmanesh, 2006;Romero-Riaño et al, 2019y Chaudhuri et al, 2020. Estas son identificadas en la literatura de cadena de suministro como colaboración horizontal, vertical y lateral (Rethemeyer, 2005;Cheikhrouhou et al, 2010y Dini, 2010.…”
Section: Redes Colaborativas (Collaborative Network Cn)unclassified
“…The number of clusters is generated automatically by the VOSviewer algorithm using the normalization function [28]. This function compares the frequency of occurrence of a node (country, word) concerning the total occurrences of the analysed set [29], [30].…”
Section: Scientific Publications Evolutionmentioning
confidence: 99%